BUDIDAYA LEBAH MADU TRIGONA SP DI KECAMATAN OBA TIDORE KEPULAUAN STUDI KASUS DI DESA KUSU SINOPA - Husen, Nining; Niapele, Sabaria; Salatalohy, Asiah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to obtain information about the trigona sp honey bee cultivation process developed by farmer groups in the village of kusu sinopa. This research was conducted in the village of kusu sinopa in September to oktober 2018 to find out trigona sp honey bee cultivation in oba sub districk, tidoreisland. Case study in the village of kusu sinopa. Informantswere taken as many as six people, they are: the head of the tidore island production forestmanagement unit (KPHP), secretary of tidore island production forest management unit (KPHP). Village head kusu sinopa. Chairmant of the honey bee farmer group. the secretary of honey bee farmer group. member of the honey bee farmer group. The results of this study indicate that the noney bee cultivation process in the village developed by farmer groups starts from the collections of colonies. Removal of colonies, keeping clean of honeybee cages/boesuntil until the direct harvesting process.